Hubungan Anemia Kehamilan Dengan Kejadian Berat Badan Lahir Rendah (BBLR): Systematic Literatur Review - Sri Wahyuni; Yustina Ananti; Chentia Misse Issabella (Journal of Health (JoH), 2021)
Pregnancy anemia has a contribution to the incidence of Low Birth Weight (LBW). The incidence of pregnancy anemia in Indonesia in 2013 was 37.1% and in 2017 it increased to 48.9%. The incidence of LBW birth in developing countries is 95.6%, and LBW is one of the causes of neonatal mortality in Indonesia. The neonatal mortality rate (IMR) in 2012 of 19 / 1,000 KH decreased in 2017 to 15 / 1,000 live births (KH), but this figure has not yet reached the SDG's (Sustainable Development Global Goals) target of 12 / 1,000 KH. The aim of this study was to determine the relationship between anemia in pregnancy and the incidence of LBW. This study uses the Systematic Literature Review (SLR) method. The sample used is 13 international and national journals using data based on Google scholar, Pubmed and NCBI. Result This study showed that 92.3% (12 journals) had a correlation between pregnancy anemia and the incidence of low birth weight. The biggest cause of pregnancy anemia based on the journal is iron deficiency (46.1%), followed by education level of 7.6%, low economic status (7.6%), and nutrition (7.6%). The incidence of LBW from anemic mothers in pregnancy was 92.3%. The conclusion of this study is that there is a relationship between pregnancy anemia and the incidence of LBW.